A study of timed get up and go scores as falls risk assessment in elderly in a tertiary care centre - Kumar, Anita; Biswas, T. K. (International Journal of Research in Medical Sciences, 2020)
Background: Early detection of falls risk in the community dwelling elderly helps to take preventive measures to avoid falls and hence decrease morbidity associated with falls. Falls are a serious threat to independent living and self-confidence of the elderly. Using simple tools to determine risk of falls helps in early detection and prevention of falls. Aims and objectives of the study was to establish TUG data among patients attending the geriatric clinic at MGM hospital, Kamothe and to determine risk of falls in these patients with respect to their systemic involvement. Methods: A prospective observational study of 100 geriatric age group patients were studied for their TUG scores and classified based on systems involved. TUG was performed using standard protocol and scores were stratified based on gender, age and diagnosis. Participants were required to perform TUG and were instructed to rise from an armless chair walk 3 meters and turn around at the chalk mark, walk back, and sit. They were instructed to walk at a normal pace without walking aids and shoes. Time was recorded when participants’ buttocks were lifted off the chair to stand and stopped when the buttocks touched the seat when returning to sitting position. Results: The results showed that the average TUG score of this cohort of 100 patients attending our geriatric outpatient clinic was 13 sec. 60 Males and 40 females were analyzed of which 38 patients had less than 12 s as TUG score and 62 patients had more than or equal to 12 sec as TUG score. Maximum number of patients undergoing the TUG test had musculoskeletal complaints. Yet patients with respiratory conditions had the highest mean TUG score of 14 sec and patients with abdominal and CNS conditions had lowest mean TUG scores. Conclusions: This study of TUG score of cohort of 100 patients showed that average TUG score was 13 sec which was higher than 12 second mark which indicates that these patients who did not have any previous fall had a risk of future falls and hence a requirement of an in depth mobility assessment and early intervention.